Penerapan Augmented Reality (AR) Pada Ikon Kabupaten Tanah Laut - Rifai, Muhammad; Aprilia, Murni; Sayyidati, Rabbini (Journal Information Technology Trends (JITRENDS), 2023)
Landmark is a city architecture that through the locality of the city has been used as an object of building, architecture or has become the identity of a city. Landmarks are usually in the form of distinctive buildings that make people know the origin of the city just by looking at it. In everyday life, many people do not recognize Ikons, Landmarks or markers in their cities, regions or countries. Many people in Tanah Laut Regency only know through TV media or when they driving on the highway they see one of these Ikons or Landmarks, so they do not know more about the Ikons or Landmarks from their area, resulting in a lack of knowledge of their own regional identity. One solution to this problem is the use of Augmented Reality (AR) technology, this technology will combine 3D designs from regional Landmarks in Tanah Laut Regency and a little explanation about this building or Ikon. In building the application, the author uses the Waterfall model using the C# programming language and is designed using Flowcharts and DFD. Application of Augmented Reality on Landmarks / Icon of Tanah Laut Regency can make it easier for the public to access information about the history and shape of the monuments in Tanah Laut Regency.